Relationship between Febrile Seizures and Iron Deficiency Anemia in Children - Kadhem, Roua Hameed; Tarish, Ali Kadhem (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The febrile seizure is the most common type of seizures occur in children under 5 years old and the peak age is 18 months, the temperature of body 38°C or more with no neurological infection or metabolic disorder. AIM: The aim of the present study is to found the association between iron deficiency anemia (IDA) and febrile seizure. METHODS: A case–control study has been carried out to determine the association between febrile convulsion and IDA. One hundred and twenty-two children with febrile seizure and 130 healthy babies include in study, period of study from May 2019 to December 2019 in Bunt Al Huda teaching hospital Nasiriyah, Dhi Qar, Iraq. The sociodemographic data are age of babies, weight, and gender. Diagnosis of febrile seizure done after details history and examination. Children aged 6 months–5 years presenting with febrile convulsion for cases and controls group of same age with fever but no convulsion. Both first and recurrent episodes of FC were included for cases. RESULTS: A case–control study of 122 children with seizures and 130 children without seizures, seizures babies have more weight than non-seizures, convulsion babies have low mean corpuscle volume than non-seizures, and seizures babies have low serum ferritin than non-seizures. There is a significant difference between mean serum ferritin of seizures and non-seizures babies, seizures babies have low serum ferritin than non-seizures. CONCLUSION: Serum ferritin also decreases more in babies with febrile seizure so IDA is occurring more in febrile seizure, and there is an association between iron supplements deficiency and febrile seizure.